Towards a Critical Pedagogy of Peace Education - Shapiro, Svi (Wydział Studiów Edukacyjnych Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2015)
This article tackles the issue of critical pedagogy in regards to education for peace. Peace education is here seen as a holistic process of development of human potential to coexist in a less violent manner. This problem is significant for example in the context of South Africa, which is being explained in this paper. Another example of this kind of pedagogy is related to the Jewish and Greek concepts of Tikkun Olam and Parrhesia. Finally they are being emphasized the issues of empathy and pedagogy pf hope.
W stronę pedagogiki krytycznej edukacji dla pokoju
Keywords: critical pedagogy; pedagogy of hope; peace education; Paulo Freire